1997
DOI: 10.1103/physrevb.56.12033
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy restoration of Fermi-liquid behavior for two-channel Kondo scattering

Abstract: The origin of zero-bias anomalies ͑ZBA's͒ in pure metal nanoconstrictions is investigated. It is shown that the ZBA's in titanium nanoconstrictions can be completely understood in terms of electron-assisted tunneling systems. The behavior of such a system is expected to depend on two distinct energy scales, a Kondo energy below which the electrons behave in a non-Fermi-liquid manner, and a splitting energy below which the Fermi-liquid behavior is restored. Titanium nanoconstrictions have been found to exhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 20 publications
2
38
0
Order By: Relevance
“…The qualitative features of these anomalies (such as their behavior in a magnetic field, under annealing and upon the addition of static impurities), which are reviewed in detail in the present paper, lead to the proposal [1] that the ZBAs are caused by a special type of defect in the nanoconstrictions, namely two-level systems (TLSs). This proposal has recently received strong support from a number of subsequent, related experiments (briefly reviewed in section VII) by Upadhyay et al on Ti constrictions [19] and by Keijsers et al on metallic-glass constrictions [20,21].…”
mentioning
confidence: 89%
See 4 more Smart Citations
“…The qualitative features of these anomalies (such as their behavior in a magnetic field, under annealing and upon the addition of static impurities), which are reviewed in detail in the present paper, lead to the proposal [1] that the ZBAs are caused by a special type of defect in the nanoconstrictions, namely two-level systems (TLSs). This proposal has recently received strong support from a number of subsequent, related experiments (briefly reviewed in section VII) by Upadhyay et al on Ti constrictions [19] and by Keijsers et al on metallic-glass constrictions [20,21].…”
mentioning
confidence: 89%
“…Note, though, that they do not occur in all Cu samples showing ZBAs. Moreover, recent experiments by Upadhyay et al [19] on Titanium constrictions and by Keijsers et al [20] on constrictions made from metallic glasses showed TLS-induced ZBAs with properties very similar to RB's quenched Cu constrictions, but no conductance transitions at all (see (Ti.6) and (MG.4) in section VII, where these experiments are reviewed). This suggests that conductance transitions are not a generic ingredient of the phenomenology of ZBAs induced by TLSs.…”
Section: Conductance Transitionsmentioning
confidence: 99%
See 3 more Smart Citations